PENGGUNAAN PERMAINAN EDUCATIF UNTUK MENINGKATKAN MOTIVASI BELAJAR BAHASA INDONESIA DI SEKOLAH DASAR - Desri, Desri (Universitas Sulawesi Tenggara, 2024)
This study aims to examine the use of educational games in increasing students' learning motivation in Indonesian language subjects in elementary schools. Educational games are chosen as a fun and effective learning method in stimulating student involvement. This literature study reviews previous studies that identify the positive impact of educational games on learning motivation, as well as their application in the context of Indonesian language learning. The results of the study indicate that the use of educational games can increase students' participation, language skills, and desire to learn Indonesian in a fun way.